The Practices of Emotional Mobilization. Wrestling with Emotions in Digital Communication - Sawicka, Maja (Studia Socjologiczne, 2026)
This essay focuses on the processes of emotional mobilization occurring in digital communication. It proposes that we view emotions not as states experienced by individuals, but as social practices: specific and tangible actions that incorporate emotions and render them social. This perspective, emotions cease to be an internal property of an isolated individual, and instead become a social matter – a specific pattern of response and adaptation practiced by a given community, a symbolic resource that enables the constitution of a socially meaningful experience. The digitalization of communication has resulted in the multiplication and diversification of emotions as practices. As a result, digital spaces become arenas in which diverse emotional practices clash, employed in struggles for visibility and engagement. In this essay, questions about the tools and course of emotional mobilization processes occurring online are addressed, as well as those pertaining to the social consequences of the saturation of digital communication with the practices of emotional mobilization.